A novel enhanced visible-light-driven photocatalyst via hybridization of nanosized BiOCl and graphitic C3N4. Issue 2 (18th November 2014) - Lei, Liwen; Jin, Huihui; Zhang, Qi; Xu, Jun; Gao, Da; Fu, Zhengyi
Abstract : Nanosized C3 N4 /BiOCl composite photocatalysts were synthesized via a facile solvothermal method in the presence of arabic gum. A possible photocatalytic mechanism over C3 N4 /BiOCl composite photocatalysts is proposed by combining photosensitization and photocatalysis. Abstract : Nanosized C3 N4 /BiOCl composites were synthesized via a facile method in the presence of arabic gum. Arabic gum acts as the structure-directing agent and helps the formation of BiOCl nanoparticles. A significant enhanced photodegradation is observed and a possible mechanism is proposed by combining photosensitization and photocatalysis.